Efficiency of Solar Domestic Hot Water System: The Case of Famagusta Northern Cyprus - Shemshaki, Meysam Saveh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Due to the Cyprus’s climate and geographical potential, the ideal energy source for obtaining power is solar energy. The main aim of this research is the development and validation of a new methodology for installation of solar thermal collectors on rooftops to achieve higher performance. This methodology follows of solar geometry and local parameters. Therefore, because of plenitude of mid-rise residential buildings in Famagusta City, two cases including Haci Ali multi-story building and Social Housing Building are analyzed. Cyprus has no energy resources of its own. Therefore, more than 94% of the total primary energy is imported to the island. High cost energy consumption due to lack of consideration in design and construction phases and available free source of solar energy are important issues here. The flat plate collectors are typically connected in rows or parallel form designs so that the desired design would be achieved to provide the temperature for a given application. It has proved that the collectors do not work as well while sun duration that causes decreasing the rate of irradiant solar absorption in winter is the main problem of this thesis. The performance of thermal solar system was calculated by the performance of water storage tank volume. No changes occurred with regard to the height and width ratio (diameter) of the water storage tank. Obviously, a capacity of 150 liter is desirable for solar thermal system. The overall performance of the solar system will be affected if the volume of storage tank is increased or decreased. It is worth noting that, shading impact due to surrounding elements or neighbor buildings is another problem resulting to less energy performance for the mentioned collectors. In other words, collectors are not able to provide hot water for residential buildings when climatic seasonal and architectural parameters restrain absorption rate of solar energy by collectors in Famagusta city.

ÖZ: Kıbrıs'ın iklimi ve coğrafi potansiyeli nedeniyle , enerji elde etmek için güneş enerjisi ideal bir enerji kaynağıdır. Bu araştırmanın temel amacı, yüksek performans elde etmek amacı ile çatılara güneş enerjisi kollektörleri kurulumu için yeni bir metodoloji geliştirmiş ve uygulanmıştır. Ayrıca bu metodoloji güneş geometri ve yerel parametrelerini izler. Bu nedenle, Mağusa şehrinde verimlilik açısından orta katlı konutlar arasında Hacı Ali çok katlı bina ve Sosyal Konut Binası olmak üzere iki olgu incelenmiştir. Kıbrıs herhangibir enerji kaynağına sahip değildir. Bu nedenle toplam enerji ihtiyacının % 94” ü dışardan alınır. Tasarım eksikliği ve doğru incelenmemesi sebebiyle mevcut tasarımlar yüksek oranda verimli enerjiyi elde edememesi ve güneş enerjisinin sınırsızca heryerde elde edilebilmesi burdaki iki önemli problem sayılır. Genellikle yassı kollektörlerin bağlantıları satır veya parallel formdadır böylece istenilen tasarım verilen uygulamalar için gereken sıcaklığı üretebilmektedir. Bu tezin asıl problemi mevcut kollektörlerin güneşli saatlerde verimli çalışmaması bu nedenle kış aylarında güneş emiliminin azalmasıdır. Termal güneş sisteminin performansı su deposu performansı üzerinden hesaplanmıştır. Su depolama tankının yüksekliği ve genişliği oranında herhangibir değişiklik yapılmadı. Net görülüyorki su deposu için 150 litre solar sistemlerde ideal bir hacimdir. Depolama tankının hacmini arttırıp azaltmak güneş sisteminin genel performansını etkileyebilir. Mevcut kollektorlerin performansının düşmesindeki ayrıca neden olarak çevre elemanlarıdır bunlar komşu binalarının gölgelendirmesi veya başka çevre faktörleri olabilir. Diğer bir deyişle, Famagusta şehrinde, mevsimsel değişiklikler ve mimari hatalardan dolayı kollektörlerin güneş enerjisi üretme performansı azalmıştır.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2016. Supervisor: Assist. Prof. Dr. Harun Sevinç.
Keywords: Architecture Department; Solar energy; Buildings--Energy conservation--Solar Energy--Hot Water Systems--Famagusta (Cyprus, North); Solar collectors--Design and construction; Solar Thermal Collector; Energy Performance; Solar Absorption; Orientation; Shading Problem